Media Censorship And Youth Participation: An Assessment Of The 2023 Elections (Journal of Namibian Studies : History Politics Culture, 2023)
The emergence of digital media has transformed information sharing and electoral processes, prompting government censorship. This study observes the impact of the 2021 Twitter ban on youth participation in Nigeria's 2023 elections, by placing a spotlight on Lagos. Utilizing quantitative analysis, the research drew on political socialization theory to understand the phenomenon of civic engagement.  A structured questionnaire was employed via a cross-sectional survey of 310 respondents and analyzed with descriptive and inferential statistics (Simple Linear Regression, ANOVA). The findings observe the impact of the Twitter ban on youth engagement in the 2023 elections and the work concludes that social media can shift youth participation from digital to physical engagements, it also recommends that social media platforms should be used to stimulate further youth engagement.